The circulation of pathogen trichinellosis and sparganosis on territories of Kursk region and human`s risk infection - N. S. Malisheva; N. A. Vagin; N. A. Samofalova; A. S. Elizarov (Российский паразитологический журнал, 2016)
The factors of trichinellosis and sparganosis pathogen circulation as typical zoonotic diseases on the territiry of Kursk region are studied. Trichinella spp. cir- culates in natural biocoenosis among predacious mammals, wild boars and rodents and sometimes infects sinanthropus animals what gives evidence of human infec- tion. Parasitical system of sparganosis in Kursk region includes definitive (wolf, fox), intermediate ( Mesocyclops leuckarti, M. obsoletus ) and supplemental (wild boar, grass snake, marsh frog, moor frog) carriers. There is a risk of sparganosis infection when using water containing cyclops and infected meat